Reconstruction of the large columella defect with Schmid-Meyer flap - Dimitrijević, Milovan; Jović, Marko; Stojković, Goran; Dimitrijević, Ana (Vojnosanitetski pregled, 2023)
Introduction. The reconstruction of columella defects is still regarded as a challenging procedure due to the very specific anatomy of the columella and limited local and regional flap options. Furthermore, the texture and color of columella tissue pose difficulties in choosing the right method of reconstruction. Case report. The report presents a patient who underwent reconstruction of a complex columella defect using a Schmid-Meyer flap. Schmid-Meyer flap represents a tubular flap with an internal supraciliary pedicle which allows the transposition of the temporal skin with the addition of ear cartilage on the tip of the nose or the ala nasi. The integration of the flap was complete. During the five-year follow-up period, the cosmetic and functional results were satisfying. Conclusion. Schmid-Meyer flap may be one of the best options for the reconstruction of complex defects of the columella.
Keywords: nasal septum; nose deformities, acquired; nose neoplasms; reconstructive surgical procedures; rhinoplasty